Scientific Papers by Developmental Biologists in Japan - Ohuchi, Hideyo; Nohno, Tsutomu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, "Scientific Papers by Developmental Biologists in Japan", represents a collection of high-quality review articles, research articles, and communications on the development of multicellular organisms at the molecule, cell, tissue, organ, and whole-organism level, which were written and submitted by developmental biologists working in Japan.